Recent cancer incidence trends in Ukraine and short-term predictions to 2022. (April 2020) - Ryzhov, Anton; Bray, Freddie; Ferlay, Jacques; Fedorenko, Zoya; Goulak, Liudmyla; Gorokh, Yevgeniy; Soumkina, Olena; Michailovich, Yuriy; Znaor, Ariana
Highlights: The incidence rates of the common cancers in Ukraine were increasing during 2003–2012. We predict an overall 18 % increase in the number of cancer cases from 2012 to 2022. While tobacco control has been implemented, there is a need for a broader cancer control plan. Abstract: Background: Using data from the National Cancer Registry of Ukraine (NCRU), we analyzed recent trends in incidence rates (2003–2012) and used these to predict the future cancer incidence burden up to 2022. Methods: All cancer cases (excluding non-melanoma of skin) for the years 2003–2012 were retrieved from the NCRU's database ( n = 1, 459, 851). Age-standardized incidence rates (ASRs) were estimated and the numbers of new cases and incidence rates predicted for 2022 using age–period modeling. Results: ASR increased from 2003 to 2012 for most cancers except lip and stomach cancers (in both sexes) and laryngeal and lung cancers (in males). Assuming these trends will continue, lung cancer will remain the most common male cancer in 2022 (ASR 40.5/100, 000), followed by prostate cancer (36.8/100, 000), colorectal cancer (34.6/100, 000), and cancers of the oral cavity and pharynx (18.5/100, 000). In females, the order of the four most common cancers will not change in 2022 compared with 2012, with cervical cancer remaining the fourth most common cancer (17.5/100, 000). We predict an overall increase of 18 % in the number of cancer cases in Ukraine (relative to 2012) to 179, 493 cases in 2022. Conclusion: The anticipated increase in the number of cancer patients in Ukraine clearly has knock-on effects on a healthcare system undergoing reforms. Tobacco control appears to be the only functioning aspect of cancer prevention in the country, and there is a need for a broader national cancer control plan. The continued monitoring and evaluation of implemented cancer control measures by the NCRU will help prioritize targets and allocate future resources to cancer services.